2005
DOI: 10.1097/01.jsm.0000179233.17885.18
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With the Use of Corticosteroids in the Treatment of Athletic Injuries

Abstract: This critical review reveals that the existing medical literature does not provide precise estimates for complication rates following the therapeutic use of injected or systemic corticosteroids in the treatment of athletic injuries. Tendon and fascial ruptures are often reported complications of injected corticosteroids, whereas tibial stress fractures and multifocal osteonecrosis were described with systemic corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(171 citation statements)
references
References 91 publications
0
153
0
3
Order By: Relevance
“…Indeed, the use of non-steroidal anti-inflammatory drugs (NSAIDs) is contraindicated for patients with fracture bone injuries and spinal fusion surgeries. 8,[23][24][25] NSAIDs have been also shown to reduce bone formation following cementless hip replacement surgery. 26 Jones et al 27 found that NSAIDs impaired angiogenesis in an aortic ring assay.…”
Section: Temporally Controlled Delivery Of Anti-inflammatory Drugsmentioning
confidence: 99%
“…Indeed, the use of non-steroidal anti-inflammatory drugs (NSAIDs) is contraindicated for patients with fracture bone injuries and spinal fusion surgeries. 8,[23][24][25] NSAIDs have been also shown to reduce bone formation following cementless hip replacement surgery. 26 Jones et al 27 found that NSAIDs impaired angiogenesis in an aortic ring assay.…”
Section: Temporally Controlled Delivery Of Anti-inflammatory Drugsmentioning
confidence: 99%
“…There are not many papers in the literature dealing with this issue, but it has been demonstrated that tendon ruptures are more frequent after local infiltration of corticosteroids [3]. This occurs due to a direct toxic effect of the drug, because corticosteroids inhibit production of extracellular matrix collagen and also because of poor local vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…However, corticosteroids also cause adverse effects including osteoporosis, and they have a local immunosuppressive effect which increases the risk of infections as well as the risk of partial and complete tendon rupture [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…[1,[9][10][11][12][13][14] Kortikosteroid enjeksiyonları PF rüptürlerinde sorumlu tutulan bir faktör olsa da, enjeksiyon sonrası rüptür oranının düşük olduğu söylenebilir. Kim ve ark., kortikosterid enjeksiyonu ile tedavi edilmiş 120 plantar fasiitis hastasını geriye dönük olarak değerlendirdikleri çalışmalarında, sadece üç olguda rüptür rapor etmişlerdir.…”
Section: Sporcularda Plantar Fasya Rüptürleriunclassified